1991
DOI: 10.3168/jds.s0022-0302(91)78425-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood and Plasma Amino Acid Uptakes by Lactating Bovine Mammary Glands

Abstract: The objective of the experiment was to determine the contribution of red blood cells to transport of individual amino acids to lactating bovine mammary glands. Blood samples were collected from coccygeal and subcutaneous abdominal veins of 21 lactating Holstein cows on d 35, 70, 105, and 126 of lactation. Samples were collected every 20 min for 12 h. Subsamples of whole blood and plasma were pooled by hour and day. Hourly plasma samples and daily whole blood and plasma samples were analyzed for amino acid conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…During LM infusion, erythrocytes might serve as a carrier for AA, supplying Lys to the mammary gland. Indeed, Hanigan et al (1991) showed, in dairy cows, that the uptake of AA (including Met and Lys) by the mammary gland differs between whole blood and plasma pools. Erythrocyte and plasma exchanges were also found to occur and plasma uptake therefore may inadequately represents whole blood uptake.…”
Section: Discussionmentioning
confidence: 99%
“…During LM infusion, erythrocytes might serve as a carrier for AA, supplying Lys to the mammary gland. Indeed, Hanigan et al (1991) showed, in dairy cows, that the uptake of AA (including Met and Lys) by the mammary gland differs between whole blood and plasma pools. Erythrocyte and plasma exchanges were also found to occur and plasma uptake therefore may inadequately represents whole blood uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the difference in flux of glutamate and glutamine in the red blood cells of the fed compared to unfed pigs suggests that this blood pool has a specific counter current role to that of plasma in transporting amino acids destine for deamination to a-ketoglutarate and subsequent glucose synthesis in the liver. Hanigan et al (1991) discussed the counter current role of red blood cells for transporting amino acids in the opposite direction of the plasma free amino acid pool in dairy cows. Red blood cells may also have an ancillary function in the renal-intestinal transport and exchange of urea cycle intermediates based on the concentrations of citrulline and ornithine in the arterial red blood cells of the fed pigs.…”
Section: Plasmamentioning
confidence: 99%
“…On the other hand, total concentration of amino acids in the arterial red blood cells of fed compared to unfed pigs suggest that this blood pool also has a role in the transport of free amino acids that has been reported for other animals. For instance, transport of amino acids in red blood cells have been reported in cattle (Hanigan et al, 1991;Koeln et al, 1993), dogs (Elwyn, 1966;Elwyn et al, 1968), sheep (Young and Ellory, 1977;Heitmann and Bergman, 1980) and humans (Felig et al, 1973). Moreover, the difference in flux of glutamate and glutamine in the red blood cells of the fed compared to unfed pigs suggests that this blood pool has a specific counter current role to that of plasma in transporting amino acids destine for deamination to a-ketoglutarate and subsequent glucose synthesis in the liver.…”
Section: Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…The Fick method is still widely used (Hanigan et al, 1991;Hanigan et al, 1992;Cant et al 1993), though several of the necessary assumptions are often invalid over short time periods. Blood flow to any organ is usually variable over time (Mepham, 1982), and arterial concentration of most metabolites varies with time, influenced largely by stage of lactation and the cows feeding regime.…”
Section: Blood Flowmentioning
confidence: 99%